Deductibility of the Spending Linked to the Expenditures Incurred as a Result of an Extrajudicial Transaction: Are We in the Face of a True Act of Liberality? - Tello Puerta, Fernando (2014)
This essay pretends to offer a juridical analysis of recent pronouncements of the Peruvian Tax Adminstration, by virtue of which, such entity states that those disbursements linked to extra judicial transactions do not constitute deductible expenses for the calculation of the Peruvian Income Tax. Under such premises, we offer a civil analysis of the nature of such disbursements and later, cover the issue of their relation with the generation of taxable income for Income Tax purposes.